2021
DOI: 10.3389/fneur.2021.653267
|View full text |Cite
|
Sign up to set email alerts
|

Serum BDNF as a Potential Biomarker of Alzheimer's Disease: Verification Through Assessment of Serum, Cerebrospinal Fluid, and Medial Temporal Lobe Atrophy

Abstract: There is an urgent need to establish blood biomarkers for Alzheimer's disease (AD). Although it has been speculated that brain-derived neurotrophic factor (BDNF) is associated with AD, whether it can be used as a blood biomarker has yet to be determined. We used serum, cerebrospinal fluid (CSF), and medial temporal lobe atrophy from patients with AD to evaluate the association of BDNF with AD and assess its severity. For the blood analysis, 66 participants [21 normal controls (NCs) with normal cognitive functi… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

2
26
0
1

Year Published

2021
2021
2024
2024

Publication Types

Select...
10

Relationship

0
10

Authors

Journals

citations
Cited by 46 publications
(37 citation statements)
references
References 32 publications
2
26
0
1
Order By: Relevance
“…Brain-derived neurotrophic factor (BDNF) regulates neuronal development, differentiation, and survival by protecting against tau-related neurodegeneration [ 47 ] and is critical to brain health [ 48 , 49 ]. However, deficient BDNF activity underlies neurodegeneration in AD, although exactly how BDNF participates in AD pathology remains unclear.…”
Section: Discussionmentioning
confidence: 99%
“…Brain-derived neurotrophic factor (BDNF) regulates neuronal development, differentiation, and survival by protecting against tau-related neurodegeneration [ 47 ] and is critical to brain health [ 48 , 49 ]. However, deficient BDNF activity underlies neurodegeneration in AD, although exactly how BDNF participates in AD pathology remains unclear.…”
Section: Discussionmentioning
confidence: 99%
“…Significantly, higher BDNF expression reduces cognitive impairment in the elderly. In addition, advanced neuropathology of AD suggests that BDNF levels in the brain can be used as a new marker to assess the progression of AD ( Mori et al, 2021 ). In vitro and in vivo experiments show that BDNF has neuroprotective effects against the cytotoxic effects of beta-amyloid plaques and Aβ-induced learning disabilities ( Jiao et al, 2016 ).…”
Section: Discussionmentioning
confidence: 99%
“…Observational studies have demonstrated that patients with AD have lower serum levels of BDNF than healthy controls ( Ng et al, 2019 ) and it has been hypothesized that this deficiency could play a role in the onset of AD neurodegeneration ( Giuffrida et al, 2018 ). BDNF is currently being studied as a potential biomarker for early detection of AD ( Mori et al, 2021 ) and is being used as a gene therapy in a phase I trial of patients with AD. ( LaFee, 2021 )…”
Section: Discussionmentioning
confidence: 99%